The contribution of syndemic conditions to cardiovascular disease risk. Issue 5 (4th May 2021) - Rodriguez, Violeta J.; Chahine, Antonio; Parrish, Manasi S.; Alcaide, Maria L.; Lee, Tae Kyoung; Hurwitz, Barry; Sawhney, Manisha; Weiss, Stephen M.; Jones, Deborah L.; Kumar, Mahendra
ABSTRACT: The syndemic conditions of low education, childhood maltreatment, depression, HIV, alcohol and cocaine use, and obesity have been established as independent risk factors for cardiovascular risk, but research examining the association between syndemic conditions and cardiovascular risk in high-risk populations is lacking. A total of N  = 503 participants underwent an ultrasound of the carotid artery to assess for atherosclerotic plaque. Participants, HIV-infected ( n  = 202) and HIV-uninfected ( n  = 301) with and without a history of cocaine use, were a mean age of 36.13 years (SD = 9.51); 50% were male, and 62% were African-American. Each syndemic condition was associated with 8% greater odds of atherosclerotic plaque (OR = 1.08), 9% greater odds of systolic blood pressure (OR = 1.09), and 10% greater odds of diastolic blood pressure (OR = 1.10). Multilevel research, interventions, and public policy initiatives are needed to activate stakeholders at each level to maximize their impact at a community level among populations with high rates of syndemic conditions.